Proceedings of the Management Science Operations Research Seminar on OR : the Essential Tool for 2020, Kuala Lumpur, 27-28 Julai 1992 - Management Science Operations Research Seminar on OR : the Essential Tool for 2020 (1992 : Kuala Lumpur); Universiti Teknologi Malaysia. Fakulti Sains Komputer dan Sistem Maklumat. Jabatan Penyelidikan Operasi (Kuala Lumpur : UTM, 1992)
Telecommunications : A fertile ground for OR applications/M Naim Yunus -- Total concept approach to manufacturing competitiveness/Zainal Aripin Zakariah, How Yit Meng -- GIS - Pengurusan Maklumat Utiliti di KL/Azizah Abdul Manaf, Noriah Idris, Wardah Zainal Abidin -- Multiple criteria decision making : A new branch of OR?/Hj. Mohd. Sahar Sawiran -- Application of SAS in Analyzing the determinants of capitall flows in Malaysia/Rita Juniati Rutaff -- An analysis of general data link flow control with partial observation/Ku Ruhana Ku Mahamud, Abu Talib Othman -- Predictors of Academic Achievement in IT : case study at UUM/Md. Farid Ab. Samad, Engku Muhammad Nazri, Bidin Yatim -- The Feasibility of Integrating a PC-Based Symbolic Integration Expert System in Mathematics Classes/Abelardo C Valida, Abas Md. Said -- Kaedah penentuan penyelesaian tersaur asas awal bagi kaedah simpleks/Azmi Jaafar, Ismail Mohd -- Airline fuel planning and optimization/Mohd. Amiruddin Jumaat -- Using TOWS Matrix in strategy formulation/Siti Maimum Kamso Rafaei -- Putting JIT into perspective/Anantha Balasundram -- Simulation of assembly line and line balancing/Faridah Maarof, Lee Yew Meng -- Optimization of port facilities/Makaraksha Saha, Anwarul Haque, Shahnor Basri, Rosnah Mohd Yusuff